Business and administrative communication - Locker, Kitty O.; Kienzler, Donna S. (McGraw-Hill/Irwin, 2013)
Focuses on the rhetorical emphases of audience, purpose, and context to allow communicators to shape their messages more appropriately to all channels and for all purposes. This title covers the topics in all forms of business communication.